Invisible cyclists? Disabled people and cycle planning – A case study of London. (March 2018) - Andrews, Neil; Clement, Isabelle; Aldred, Rachel
Abstract: This paper reports on analysis of over 50 London transport and cycling strategy documents. Both image and text were analysed, in exploring representations of disabled people, particularly as cyclists or potential cyclists. It remains unusual for disabled people's cycling to be considered within broader transport strategy documents; instead they are overwhelmingly conceptualised as public transport users and pedestrians. By contrast it was more usual for cycling strategies to at least mention disabled people as cyclists or potential cyclists. However, discussion of policies that might increase disabled people's participation in cycling was often limited to general aspirations or references to leisure cycling clubs and training. Few images in cycling strategies (and even less so transport strategies) showed non-standard cycles of the kind used by some disabled cyclists. Disabled people's cycling (and barriers to cycling) needs further research and a policy approach that targets social and structural exclusion from cycling, not only individual ability and attitudes. More thought needs to be given to a range of types of disability and how these might affect cycling needs. Highlights: Paper analyses images and text from over 50 London transport and cycling strategies Few images, particularly from transport strategies, depicted non-standard cycles Some cycling strategies, but few transport strategies, mentioned disabled cyclists Such mentions were often general aspirations or referred to leisure clubs and training Greater attention should be paid to reducing barriers to disabled people's cycling